Beyond oil and gas : the methanol economy - Olah, George A. (George Andrew), 1927-2017; Goeppert, Alain, 1974-; Prakash, G. K. Surya (Wiley-VCH, 2018)
Completely revised and updated, the third edition of this bestseller discusses the concept and ongoing development of using methanol and derived dimethyl ether as a transportation fuel, energy storage medium, and as a chemical raw material to replace fossil fuels. The contents have been expanded by 35% with new and up to date coverage on energy storage, methanol from biomass and waste products, as well as on carbon dioxide capture and recycling. Written by the late Nobel laureate George Olah, Alain Goeppert and G.K. Surya Prakash, this is an inspiring read for anyone concerned with the major challenge posed by environmental problems including global warming and ocean acidification due to massive increase in fossil fuel use. The book provides a comprehensive and sustainable solution to replace fossil fuels in the long run by chemical recycling of carbon dioxide through renewable methanol utilizing alternative energy sources such as solar, wind, hydro, geothermal and nuclear. The Methanol Economy is being progressively implemented in many parts of the world.